Dynamics of Toxoplasma gondii Oocyst Phagocytosis by Macrophages - Ndao, Omar; Puech, Pierre-Henri; Bérard, Camille; Limozin, Laurent; Rabhi, Sameh; Azas, Nadine; Dubey, Jitender P.; Dumètre, Aurélien (Frontiers in Cellular and Infection Microbiology, 2020)
Oocysts are the environmentally resistant stage of the protozoan parasite Toxoplasma gondii. They are responsible for foodborne infections in humans and animals worldwide. Infectious oocysts contain sporozoites that have to exit the sporocyst and oocyst walls to initiate replication of the parasite within the host tissues. Given their robustness and resistance to chemical degradation, it is still unclear how the oocyst and sporocyst walls release the sporozoites. This process called excystation is thought to occur in the small intestine as a result of the combined action of digestive agents, yet to be identified. By using an oocyst-macrophage co-culture platform, we previously demonstrated in vitro that the excystation of sporozoites and their differentiation into replicative tachyzoites could occur in absence of digestive factors, following phagocytosis by macrophages. Here, we further characterize the dynamics of the oocyst phagocytosis at the single-cell level by using optical tweezers and micropipette aspiration techniques. Our results show that the oocyst internalization kinetics can vary among a given population of macrophages, but similar processes and dynamics could be observed. Most of the cells manipulate oocysts for 15 min before internalizing them in typically 30 min. This process mainly involves the actin cytoskeleton of the macrophages. Liberated sporozoites within macrophages then differentiate into tachyzoites within 4 to 6 h following oocyst-macrophage contact. Tachyzoites appear to develop better in macrophages challenged with free sporocysts or sporozoites than with whole oocysts, suggesting that opening of the oocyst wall is one of the most limiting steps for sporozoite excystation completion.